1: ĐKXĐ: x>=3
\(3\sqrt{\dfrac{25x-75}{9}}+2\sqrt{x-3}-\dfrac{1}{2}\cdot\sqrt{4x-12}=12\)
=>\(3\cdot\dfrac{5}{3}\cdot\sqrt{x-3}+2\sqrt{x-3}-\dfrac{1}{2}\cdot2\sqrt{x-3}=12\)
=>\(5\sqrt{x-3}+2\sqrt{x-3}-\sqrt{x-3}=12\)
=>\(6\sqrt{x-3}=12\)
=>\(\sqrt{x-3}=2\)
=>x-3=4
=>x=7(nhận)
2:
a:
b: Tọa độ A là:
\(\left\{{}\begin{matrix}y=0\\-x+4=0\end{matrix}\right.\Leftrightarrow\left\{{}\begin{matrix}x=4\\y=0\end{matrix}\right.\)
Vậy: A(4;0)
Tọa độ B là:
\(\left\{{}\begin{matrix}x=0\\y=-x+4=-0+4=4\end{matrix}\right.\)
Vậy: B(0;4)
O(0;0); A(4;0); B(0;4)
\(OA=\sqrt{4^2+\left(0-0\right)^2}=4\)
\(OB=\sqrt{\left(0-0\right)^2+\left(4-0\right)^2}=4\)
Vì Ox\(\perp\)Oy
nên OA\(\perp\)OB
=>ΔOAB vuông tại O
=>\(S_{AOB}=\dfrac{1}{2}\cdot OA\cdot OB=\dfrac{1}{2}\cdot4\cdot4=8\)
Vì M là trung điểm của OB
nên \(S_{ABM}=\dfrac{1}{2}\cdot S_{ABO}=\dfrac{1}{2}\cdot8=4\)